A systemic whole-plant change in redox levels accompanies the rapid systemic response to wounding. Issue 1 (28th January 2021) - Fichman, Yosef; Mittler, Ron
Abstract : The wounding-induced reactive oxygen species (ROS) wave is accompanied by a systemic whole-plant redox response in Arabidopsis.